Esophageal smooth muscle reactivity is impaired in chronic reflux esophagitis by both receptor- and nonreceptor-mediated mechanisms - YEGEN, BERRAK; BOZKURT, SÜHEYLA (W B SAUNDERS CO-ELSEVIER INC, 2007)
Aim: Esophagitis is associated with an impaired esophageal peristalsis. A few studies have been aimed at understanding the pathophysiology of abnormal peristaltic activity. The mechanism of impaired esophageal smooth muscle reactivity in the chronic gastroesophageal reflux (GER) model is investigated in vitro for the first time. Materials and Methods: The chronic GER rat model was created by partial gastric outlet obstruction. The histopathological findings related to esophagitis were evaluated. Smooth muscle strips of the tunica muscularis mucosa of esophagus were studied in standard organ chambers. Carbachol- and KCl-induced contractile responses and serotonin- and papaverine- induced relaxant responses in both reflux and sham-operated control groups were determined. Results: Histopathologically, chronic reflux esophagitis was observed in all specimens of the reflux group. Contractile (carbachol- and KCl-induced) smooth muscle responses were significantly decreased in the reflux group. When compared to control group, relaxant response of smooth muscle to serotonin was also significantly decreased in the reflux group. However, there was no difference in papaverine- induced relaxant responses between 2 groups. Conclusions: Our study describes the effects of chronic GER on rat esophageal smooth muscle contractility in vitro. We found that both receptor- (carbachol, serotonin) and nonreceptor-mediated (KCl) esophageal smooth muscle reactivity were impaired in chronic reflux esophagitis. These changes may correspond to the functional motor abnormalities of the esophagus seen in patients with chronic reflux esophagitis. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: gastroesophageal reflux; smooth muscle; carbachol; serotonin; in vitro; esophagus; GASTROESOPHAGEAL-REFLUX; MOTOR ABNORMALITIES; CIRCULAR MUSCLE; DISEASE; RAT; MOTILITY; PH; FUNDOPLICATION; DYSFUNCTION; RELAXATION